2020
DOI: 10.1002/jev2.12003
|View full text |Cite
|
Sign up to set email alerts
|

EGFR‐rich extracellular vesicles derived from highly metastatic nasopharyngeal carcinoma cells accelerate tumour metastasis through PI3K/AKT pathway‐suppressed ROS

Abstract: Nasopharyngeal carcinoma (NPC) is the most common cancer with high metastatic potential that occurs in the epithelial cells of the nasopharynx. Distant metastases are the primary cause for treatment failure and mortality of NPC patients. However, the underlying mechanism responsible for the initiation of tumour cell dissemination and tumour metastasis in NPC is not well understood. Here, we demonstrated that epidermal growth factor receptor (EGFR) was highly expressed in tumour tissues of NPC patients with dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 75 publications
(80 reference statements)
0
24
0
Order By: Relevance
“…In nasopharyngeal carcinoma (NPC), EVs migrate from highly metastatic to poorly metastatic NPC cells, mediate intercellular communication, and enhance the metastatic potential of poorly metastatic NPC cells by inducing the up‐regulation of epidermal growth factor receptor (EGFR) and down‐regulation of reactive oxygen species (ROS). 191 Mechanistically, overexpression of EGFR mediated by EGFR‐rich EVs down‐regulates intracellular ROS levels through regulating PI3K/AKT pathway, thereby promoting the metastatic potential of NPC with poorly metastatic ability. 191 …”
Section: Components and Mechanisms Involved In Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…In nasopharyngeal carcinoma (NPC), EVs migrate from highly metastatic to poorly metastatic NPC cells, mediate intercellular communication, and enhance the metastatic potential of poorly metastatic NPC cells by inducing the up‐regulation of epidermal growth factor receptor (EGFR) and down‐regulation of reactive oxygen species (ROS). 191 Mechanistically, overexpression of EGFR mediated by EGFR‐rich EVs down‐regulates intracellular ROS levels through regulating PI3K/AKT pathway, thereby promoting the metastatic potential of NPC with poorly metastatic ability. 191 …”
Section: Components and Mechanisms Involved In Metastasismentioning
confidence: 99%
“… 191 Mechanistically, overexpression of EGFR mediated by EGFR‐rich EVs down‐regulates intracellular ROS levels through regulating PI3K/AKT pathway, thereby promoting the metastatic potential of NPC with poorly metastatic ability. 191 …”
Section: Components and Mechanisms Involved In Metastasismentioning
confidence: 99%
“…Recently, research showed that highly metastatic NPC cells secrete EGFR-rich extracellular vesicles (EVs) that can be absorbed by poorly metastatic NPC cells. Then, EGFR-rich EVs promote EGFR up-regulation and intracellular ROS reduction through the EGFR/PI3K/Akt pathway, thus aggravating the metastasis and progression of NPC [ 81 ]. Undoubtedly, EVs delivering EGFR or EGFR ligands promote angiogenesis, metastasis, and osteoclastogenesis in tumors, modulating the immune system and blocking these EVs’ activities to reduce drug resistance [ 82 , 83 ].…”
Section: The Role Of Egfr Pathways In Nasopharyngeal Carcinomamentioning
confidence: 99%
“…Mechanistically, on one hand, Eps8 increases p53 and decreases Src and AKT in such a way that HeLa and SiHa cells are sensitive to chemotherapeutic drugs ( 14 ). On the other hand, PI3K/AKT is an important cascade reaction of tumour chemotherapy resistance ( 120 ), and EGFR is the key to activating the PI3K/AKT signalling pathway ( 121 ). In general, EGFR TKI resistance is divided into ‘on target’ and ‘off-target’.…”
Section: Role and Molecular Mechanism Of Eps8 In Solid Tumoursmentioning
confidence: 99%